High resolution characterisation of corrosion and hydrogen pickup of Zr-Nb cladding alloys - Hu, J (2016)
Zr cladding alloys have been used for many years as the first safety barrier layer of a nuclear reactor. However, the recent Fukushima accidents and industrial demands to increase the burnup of fuels have led to increasing interest in a detailed mechanistic understanding of aqueous corrosion and hydrogen pickup and the performance at high temperatures. As part of an international MUZIC-2 programme (Mechanistic Understanding of Zr Corrosion and Hydrogen pickup), I have used a range of advanced microscopy techniques to study the microstructure, the nanoscale chemistry and the porosity in a series of zirconium alloys at different stages of corrosion and hydrogen pickup. Samples from both autoclave and in-reactor conditions were available to compare, I have focussed on RXA (recrystallised 580°C) Zr-1.0Nb and annealed (720°C) Zr-1.0Nb alloys. A set of samples from different exposures times were chosen to represent early, pre-transition and post-transition samples in order to compare the microstructure and microchemistry of the oxides, the metal-oxide interface and the metal. (Scanning) Transmission Electron Microscopy ((S)TEM), Transmission Kikuchi Diffraction (TKD) and automated crystal orientation mapping with TEM (ASTAR mapping) were used to study the grain structure and phase distribution. Significant differences in grain morphology were observed between samples oxidised in the autoclave with different corrosion rates, with more uneven metal-oxide interface, more parallel cracks and less organised oxide grains in the fast corroding samples. Comparing with autoclave samples, the in-reactor samples have shorter, less well-aligned monoclinic grains and more tetragonal grains. The rapidly oxidising annealed Zr-1.0Nb alloy also have much higher tetragonal grain fraction comparing with the slow corrosion rate RXA Zr-1.0Nb alloys. Porosity in the oxide is predicted to have a major influence on the overall rate of corrosion and hydrogen pickup, and there is much more porosity in the annealed Zr-1.0Nb alloy than found in either the RXA alloy or the similar alloy exposed to neutron irradiation. A combination of Energy Dispersion X-ray (EDX) mapping in STEM and Electron Energy Loss Spectroscopy (EELS) analysis of second phase particles can reveal the main and the minor element distributions respectively. The annealed Zr-1.0Nb alloys have β-Zr SPPs with nano crystalline structure and much larger size. Although they does not relate with the higher density of cracks in the oxide, the large SPP size can connect together all the small cracks that are generated by the huge amount of tetragonal to monoclinic phase transformation during corrosion and provides pathway for corrosion and hydrogen pickup. Two kinds of SPPs are found in the RXA Zr-1.0Nb alloys, one is β-Nb and another one is Zr-Nb-Fe Laves phase. Neutron irradiation seems to have little effect on promoting fast oxidation or dissolution of β-Nb precipitates, but encourages dissolution of Fe from Laves phase precipitates. Electron Energy Loss Spectroscopy (EELS) analysis of the oxidation state of Nb in β-Nb SPPs in the oxide revealed the fully oxidised Nb5+ state in the SPPs deep into the oxide, but Nb2+ in the crystalline SPPs near the metal-oxide interface. EELS, TKD and ASTAR mapping have also revealed the presence of suboxide layers with the hexagonal ZrO structure predicted by ab initio modelling. The combined thickness of the ZrO suboxide and oxygen-saturated layers at the metal-oxide interface correlates well to the estimated instantaneous oxidation rate, suggesting that the presence of this oxygen- rich zone combining with the part where porosity is not interconnected is the protective oxide that is rate limiting in the key in the transport processes involved in corrosion and hydrogen pickup.